1991
DOI: 10.1111/j.1151-2916.1991.tb07150.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interfacial Debonding and Matrix Cracking in the Effective Thermal Diffusivity of Alumina‐Fiber‐Reinforced Chemical‐Vapor‐Infiltrated Silicon Carbide Matrix Composites

Abstract: The thermal diffusivity of a biaxial weave alumina-fiberreinforced chemical-vapor-deposited (CVD) Sic composite heated to 1500°C, which is above the manufacturing temperature, was found to exhibit an increase for heat flow parallel to the fiber plane, whereas a decrease was observed perpendicular to the fiber plane. The increase parallel to the fiber plane was thought to be due to the annealing of the fibers and matrix. The decrease perpendicular to the fiber plane was found to be the result of interfacial deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The particulate-reinforced ceramic matrices, i.e., containing hard ceramic inclusions in a ceramic matrix exhibit several advantages compared to their single phase counterpart. A few of the advantages include attractive combinations of strength, thermal shock resistance, better wear resistance, enhanced fracture toughness, and a noncatastrophic failure mode [15][16][17]. To overcome the inherent limitations of the monolithic ceramic constituents the primary aim of this research was to consolidate fine powders of TiB 2 and B 4 C. Overall combination of the TiB 2 and B 4 C ceramics brings out the latent advantage of each while concurrently eliminating shortcomings of the individual phases.…”
Section: Introductionmentioning
confidence: 98%
“…The particulate-reinforced ceramic matrices, i.e., containing hard ceramic inclusions in a ceramic matrix exhibit several advantages compared to their single phase counterpart. A few of the advantages include attractive combinations of strength, thermal shock resistance, better wear resistance, enhanced fracture toughness, and a noncatastrophic failure mode [15][16][17]. To overcome the inherent limitations of the monolithic ceramic constituents the primary aim of this research was to consolidate fine powders of TiB 2 and B 4 C. Overall combination of the TiB 2 and B 4 C ceramics brings out the latent advantage of each while concurrently eliminating shortcomings of the individual phases.…”
Section: Introductionmentioning
confidence: 98%
“…However, these mechanisms are detrimental to other properties pertinent to thermostructural performance, especially the thermal diffusivity. 2,3 The latter property is important in determining the magnitude of thermal stresses when the material is subjected to temperature gradients and is therefore relevant to its thermal shock resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed, however, that the development of single-phase ceramics has reached its optimum stage, and the attention of researchers has now turned to develop ceramic matrix composites (CMCs). CMCs offer considerable advantages over monolithic ceramics due to their enhanced fracture toughness and noncatastrophic failure mode [1]. The TiB 2 -TiC composites prepared from pre-mixed TiB 2 and TiC powders have shown that the fracture toughness and wear resistance of the composites are significantly higher than those of the individual TiB 2 and TiC phases [2].…”
Section: Introductionmentioning
confidence: 99%